2021
DOI: 10.2196/29942
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Quality of YouTube Videos as a Source of Public Health Information Regarding COVID-19 Vaccination: Cross-sectional Study

Abstract: Background Recent emergency authorization and rollout of COVID-19 vaccines by regulatory bodies has generated global attention. As the most popular video-sharing platform globally, YouTube is a potent medium for the dissemination of key public health information. Understanding the nature of available content regarding COVID-19 vaccination on this widely used platform is of substantial public health interest. Objective This study aimed to evaluate the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Given the short development period of COVID-19 vaccines, coupled with the vaccination accidents of related vaccines, poor vaccine protective efficacy, and other facts, college students' willingness to vaccinate is easily affected by negative news about COVID-19 vaccination ( 38 ). Studies have found that the overall quality and credibility of the information about the COVID-19 vaccine on the famous video sharing platform YouTube is poor, and the false information contained therein may reduce people's COVID-19 vaccination rate ( 39 ). Jain et al suggest that it is pertinent to design an evidence-based strategy to promote the uptake of vaccination among students, which could include informational campaigns that address vaccine hesitancy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the short development period of COVID-19 vaccines, coupled with the vaccination accidents of related vaccines, poor vaccine protective efficacy, and other facts, college students' willingness to vaccinate is easily affected by negative news about COVID-19 vaccination ( 38 ). Studies have found that the overall quality and credibility of the information about the COVID-19 vaccine on the famous video sharing platform YouTube is poor, and the false information contained therein may reduce people's COVID-19 vaccination rate ( 39 ). Jain et al suggest that it is pertinent to design an evidence-based strategy to promote the uptake of vaccination among students, which could include informational campaigns that address vaccine hesitancy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, health disinformation and misinformation can easily and rapidly be spread in a digital society through social media, contributing to the continued existence and strengthening of factually incorrect health beliefs [ 26 ]. A recent notable example of health misinformation has been the tremendous decline in vaccine confidence [ 27 ].…”
Section: Impact Of Digital Technologies On the Distribution Of Inform...mentioning
confidence: 99%
“…As one of the platforms that dominate this field, it was preferred to conduct the study on YouTube. Although there is a previous YouTube study on COVID-19 vaccination, no research has been identified on COVID-19 vaccination in RD [ 7 ]. Because of the basic characteristics of their diseases and various immunosuppressive drugs they use, patients with RD should be considered separately from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing information on the Internet is one of the important sources in this regard. A considerable portion of Internet consumers has the potential to use YouTube, the second most preferred website globally after Google, to provide more and detailed information [ 7 ]. YouTube, the most popular video-sharing platform, provides a wide range of content to users, with more than 500 h of video uploaded per minute [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation